Collection of voucher specimens for bat research: conservation, ethical implications, reduction, and alternatives. (19th July 2017) - Russo, Danilo; Ancillotto, Leonardo; Hughes, Alice C.; Galimberti, Andrea; Mori, Emiliano
Abstract: Voucher specimens have played a fundamental role in biology, but ethical and conservation concerns have been raised over unnecessary collection of organisms. From 1996 to 2017, 222 studies mentioned the collection of 7482 bats of 376 species, mostly from South America and Asia (India, China, and South‐East Asia). Researchers mostly aimed to compile checklists or establish geographic ranges. Strong ethical reasons exist to avoid unnecessary collection, and suitable alternatives should be sought; for example, collecting voucher specimens for retrospective taxonomic confirmation can be replaced with molecular methods. We provide information on alternative methods and when to use them to avoid harming fragile populations of bats.